OPTIMIZATION TACTICS TREATMENT OF DESTRUCTIVE PANCREATITIS (Ta'limning zamonaviy transformatsiyasi, 2024)
Currently, acute pancreatitis (AP) took 3rd place in the structure acute surgical diseases of the abdominal cavity with a tendency of further growth of morbidity and increasing the number of its destructive forms, accompanied by a large number of complicate and high numbers mortality. [1].